(3QSGdI GdZGjI hGdfUjMIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi CejQ GdeDefjf Ld PcQg hHg CSJYjf ai LejY GdCehQ ef YHO CejQ GdeDefjf Ld PcQ ehdGfG heedhcg s
(3BNQgG (B:s
(3hGdMeO hGdTcQ dehdGfG Ld PcQg ai GdSQGA hGdVQGA hGdTOI hGdQNGA hgh GdeYjf hYdjg GdJhcd ZGjI GdbUO hGdQLGA JeJ HeO ehdGfG hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3abg GdePGgH GdCNQis